Synthesis and Electrochemical Properties of Fe2O3@C Composite - Thi Hang, Bui (VNU Journal of Science: Mathematics - Physics; Vol 34 No 4, 2018)
Abstract:   Fe 2 O 3 @C material was prepared by one-step hydrothermal method for use as a negative electrode in an iron-air battery. The structure of Fe 2 O 3 @C was determined by X-ray diffraction (XRD) measurement while their morphology was observed by scanning electron microscopy (SEM). The electrochemical properties of the Fe 2 O 3 @C electrode in alkaline solution were investigated using cyclic voltammetry (CV) measurement. The results showed that Fe 2 O 3 @C material with α-Fe 2 O 3 structure and amorphous carbon were successfully synthesized by one-step hydrothermal method. CV measurements indicate that the redox reaction rate of the Fe 2 O 3 @C electrode is higher than that of the Fe 2 O 3 @AB electrode using commercial Fe 2 O 3 and AB (Acetylene Black Carbon). Keywords: Fe 2 O 3 @C material, Fe 2 O 3 @C electrode, hydrothermal method, iron-air battery. References [1] Westinghouse Advanced Energy Systems Division, and demonstration of a nickel/ iron battery for electric vehicle propulsion, J. Power Sources 11, (1984) 315. [2] Eagle-Pitcher Industries Inc., Research, development, and demonstration of a nickel/ iron battery for electric vehicle propulsion, J. Power Sources 11, (1984) 316. [3] A.A. Kamnev, The role of lithium in preventing the detrimental effect of iron on alkaline battery nickel hydroxide electrode: A mechanistic aspect, Electrochim. Acta 41 (1996) 267. [4] J.G. Zhang, P.G. Bruce and X. G. Zhang, Handbook of Battery Materials - Chapter 22: Metal-Air Batteries, (2013) 1000. [5] D. Zhou, W.L. Song, X. Li, L.Z. Fan and Y. Deng, Tin nanoparticles embedded in porous N-doped graphene-like carbon network as high-performance anode material for lithium-ion batteries, J. Alloys Compd. 699 (2017) 730. [6] E.J. Rudd and D. W. Gibbons, High energy density aluminum/oxygen cell, J. Power Sources 47 (1994)329. [7] K. Vijayamohanan, T.S. Balasubramanian and A.K. Shukla, Rechargeable alkaline iron electrodes, J. Power Sources 34 (1991) 269. [8] A.K. Manohar, S. Malkhandi, B. Yang, C. Yang, G. K Surya Prakash. and S.R. Narayanan, A High-Performance Rechargeable Iron Electrode for Large-Scale Battery-Based Energy Storage, J. Electrochem. Soc. 159 (2012) A1209. [9] G.M. Ehrlich, Lithium-Ion Batteries, Handbook of Batteries, (2002) 35.1. [10] N. Nitta, F. Wu, J.T. Lee and G. Yushin, Li-ion battery materials: present and future, Mater. Today 18 (2014) 252. [11] Anon, Iron-air batteries for electric vehicles, J. Power Sources 5 (1980) 344. [12] L. Öjefors, Self-discharge of the alkaline iron electrode, Electrochim. Acta 21, (1976) 263. [13] K.F. Blurton and A.F. Sammells, Metal/air batteries: Their status and potential - a review, J. Power Sources 4 (1979) 263. [14] M. Lübke, N.M. Makwana, R.Gruar, C. Tighe, D. Brett, P. Shearing, Z. Liu and J.A. Darr, High capacity nanocomposite Fe3O4/Fe anodes for Li-ion batteries, J. Power Sources 291 (2015) 102. [15] T.S. Balasubramanian and A.K. Shukla, Effect of metal-sulfide additives on charge/discharge reactions of the alkaline iron electrode, J. Power Sources 41 (1993) 99. [16] U. Casellato, N.Comisso and G. Mengoli, Effect of Li ions on reduction of Fe oxides in aqueous alkaline medium, Electrochim. Acta 51 (2006) 5669. [17] B.T. Hang, M. Egashira, I. Watanabe, S. Okada, J. Yamaki, S.H. Yoon, I. Mochida, The effect of carbon species on the properties of Fe/C composite for metal-air battery anode, J. Power Sources 143 (2005) 256. [18] K. Micka, Z. Zabransky, Study of iron oxide electrodes in an alkaline electrolyte, J. Power Sources 19 (1987) 315. [19] C. Chakkaravarthy, P. Periasamy, S. Jegannathan, K.I. Vasu, The nickel/iron battery, J. Power Sources 35 (1991) 21. [20] J. Černý and K. Micka, Voltammetric study of an iron electrode in alkaline electrolytes, J. Power Sources 25(2) (1989) 111.